The mammoth - Tobin, Paul, 1965- (Mad Cave, 2024)
"Something is wrong in the deep forests of Broke Tree Valley. Something deadly. Something mammoth. The legends speak of something larger than human comprehension... A monstrous phantom that disappears for decades at a time. Now, it's back, and things are about to go very bad if four people--Olivia, Jess, Kokoro, and Mason, scientists who have come to the small city of Kasbro to investigate a bizarre series of seismic activities in this heavily forested valley--can't put the mammoth to rest. One real problem with this is... Olivia's dead"--